Total flavonoids of hawthorn leaves protect spinal motor neurons via promotion of autophagy after spinal cord injury - Zhang, Qiong; Liu, Mingfu; Nong, Haibin; Zhang, Yanan; Bai, Yiguang; Liu, Pan; Zong, Shaohui; Zeng, Gaofeng (Frontiers in Pharmacology, 2022)
Spinal motor neuron (SMN) death after spinal cord injury (SCI) is a crucial cause that contributed to a permanent neurological deficit. Total flavonoids of hawthorn leaves (TFHL) have been confirmed to have therapeutic potential for SCI. However, the roles and mechanism of TFHL in neuromotor function recovery and axonal regeneration of SMNs have not been fully elucidated. In this study, TFHL was applied to treat rats with SCI and injured SMNs for 7 days. In vivo experiment, the motor functional recovery of SCI rats was evaluated by Basso-Beattie-Bresnahan (BBB) score. The morphology, microstructure, apoptosis, Nissl bodies, and autophagy of SMNs in spinal cord tissue were detected by Hematoxylin-eosin (HE) staining, transmission electron microscopy, TUNEL staining, Nissl staining, and immunohistochemistry respectively. In vitro experiment, the co-culture model of SMNs and astrocytes was constructed to simulate the internal environment around SMNs in the spinal cord tissue. The cell morphology, microstructure, axonal regeneration, and autophagy were observed via optical microscope, transmission electron microscopy, and immunofluorescence. The content of neurotrophic factors in the cell culture medium of the co-culture model was detected by ELISA. Moreover, the axons and autophagy-related proteins expression of spinal cord tissue and SMNs were measured by Western Blot. We demonstrated that TFHL improved the neuromotor function recovery in rats after SCI. We then found that TFHL significantly promoted injured spinal cord tissue repair, reduced apoptosis, and improved the functional status of neurons in spinal cord tissue in vivo. Meanwhile, the cell morphology, microstructure, and axonal regeneration of damaged SMNs also obviously were improved, and the secretion of neurotrophic factors was facilitated after treatment with TFHL in vitro. Further, we revealed that TFHL promoted autophagy and related proteins expression in vivo and vitro. Taken together, our study suggested that TFHL might promote autophagy and exert neuroprotective effects on SMNs to promote the recovery of neuromotor function of rats with SCI.